Multi-element rare earth zirconium oxide material capable of resisting erosion of molten sand dust and preparation method of multi-element rare earth zirconium oxide material

Through the design and synthesis of diverse rare earth oxidation materials, the problem of high thermal guidance rate of heat -barrier coating materials in high temperature environments, insufficient anti -melting sand and dust erosion performance and poor thermal stability, realizing the low thermal guidance rate of materials , Excellent corrosion performance and high heat stability.

CN119371199AActive Publication Date: 2025-01-28XI AN JIAOTONG UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411584322.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-28
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

The existing thermal barrier coating materials have high thermal conductivity, insufficient resistance to molten sand dust and poor thermal stability in high temperature environments, resulting in reduced performance and premature failure in complex stress environments.

Method used

The design of multiple rare earth oxidation materials is adopted, and the non -equal ratio of the non -equal Moore ratio of Y2O3, A2O3 and B2O3 and ZRO2 forms ceramic materials with excellent mechanics, thermal science, and anti -melting sand and dust erosion. This material is synthesized by the high temperature solid reaction method, and the dense ceramic block is formed by dry pressure molding and high temperature sintering.

Benefits of technology

It significantly reduces the heat conduction coefficient of the material, improves the thermal insulation performance of the coating, and provides better anti -melting sand and dust erosion performance and thermal stability, and extends the service life of thermal obstacle coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371199A_ABST
    Figure CN119371199A_ABST
Patent Text Reader

Abstract

The invention discloses a multi-element rare earth zirconium oxide material resistant to molten sand and dust erosion and a preparation method thereof, and belongs to the technical field of aero-engine thermal barrier coating materials. ZrO2, a main rare earth oxide Y2O3 and auxiliary rare earth oxides A2O3 and B2O3 are used as basic raw materials, the basic raw materials are precisely proportioned, ball-milled and mixed, the multi-element rare earth zirconium oxide material is synthesized by adopting a high-temperature solid-phase reaction method, the material shows the structural characteristics of a defective fluorite phase, a compact ceramic block is prepared by utilizing dry-pressing molding and high-temperature sintering processes, and the ceramic block has the characteristics of high-temperature sintering, high-temperature sintering, high-temperature sintering, high-temperature sintering, high-temperature sintering and high-temperature sintering. By investigating the molten sand dust corrosion resistance, the performance is excellent, the thermal conductivity is low, and the high-temperature stability is high. The material is suitable for being applied to thermal barrier coating materials of aero-engine hot end components, the high-temperature molten sand dust corrosion resistance of the thermal barrier coating materials is remarkably improved, and the service life of the thermal barrier coating materials is remarkably prolonged. The technical problems that a thermal barrier coating material is high in thermal conductivity, insufficient in molten sand dust corrosion resistance and poor in thermal stability are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal barrier coating materials for aviation engines, and in particular relates to a multi-component rare earth zirconium oxide material resistant to molten sand and dust erosion and a preparation method thereof. Background Art

[0002] The thermal barrier coating on the surface of high-temperature alloy components that operate for a long time in the high temperature and high pressure of aircraft engines and harsh turbine environments must have low thermal conductivity, high thermal insulation, and good fracture toughness to improve the strain tolerance of the coating in complex stress environments. With the further requirements for high efficiency of aircraft engines, higher surface temperatures have brought new challenges to thermal barrier coatings. During service, thermal barrier coatings must not only withstand high temperatures and high air pressures, but also withstand erosion from environmental pollutants such as dust and sand (CMAS). CMAS deposits will melt, penetrate and react with TBC, thereby reducing the thermomechanical properties of TBC and causing premature failure. In particular, the sand and dust components from the environment are more complex, and the melted sand and dust will cause more serious erosion and damage to the thermal barrier coating, which requires the thermal barrier coating to have excellent resistance to molten sand and dust erosion.

[0003] Traditional YSZ (yttria-stabilized zirconia) materials will chemically react with the molten CMAS attached to its surface, resulting in coating phase instability and structural damage. Studies have shown that rare earth zirconate materials (such as gadolinium zirconate) are considered as one of the potential choices for thermal barrier coatings due to their lower thermal conductivity and good CMAS resistance. However, this type of material has certain limitations in its corrosion resistance (especially resistance to molten sand and dust erosion) at service temperatures above 1300°C. The rare earth elements and CMAS in the material cannot quickly form a continuous and dense barrier layer to resist high-temperature molten sand and dust corrosion, and cannot provide a reliable long-life guarantee for thermal barrier coatings. With the in-depth research on multi-component ceramic systems and the maturity of technology, ceramic materials developed through multi-component design usually show comprehensive properties that exceed those of single-component zirconia or zirconates, especially in mechanics, thermal and corrosion resistance, thus showing great application prospects in the field of aerospace high-temperature structural materials.

[0004] In view of these shortcomings of existing technologies, a high-performance thermal barrier coating material with excellent mechanical, thermal and molten sand and dust erosion resistance was developed through multi-rare earth collaborative design. The research and development of this new thermal barrier coating material is expected to improve the performance and durability of aircraft engine components, thereby promoting the development of aviation technology to a higher level. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a multi-rare earth zirconia material resistant to molten sand and dust erosion and a preparation method thereof, so as to solve the technical problems of high thermal conductivity, insufficient resistance to molten sand and dust erosion and poor thermal stability of thermal barrier coating materials.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention provides a multi-component rare earth zirconium oxide material resistant to erosion by molten sand and dust. The chemical composition of the multi-component rare earth zirconium oxide material resistant to erosion by molten sand and dust is: (xY 2 O 3 -yA 2 O 3 -yB 2 O 3 )-(1-x-2y)ZrO 2 , wherein the molar percentage x is: 17%≤x≤31%, the molar percentage y is: 1.5%<y<8.5%, and 34%≤(x+2y)≤46%; The multi-component rare earth zirconia material resistant to molten sand and dust erosion comprises zirconium oxide, main rare earth oxide Y 2 O 3 、Auxiliary rare earth oxide A 2 O 3 and auxiliary rare earth oxide B 2 O 3 , wherein the auxiliary rare earth oxide A 2 O 3 and auxiliary rare earth oxide B 2 O 3 The rare earth element A or B in the composition includes any one of Gd, Dy, Yb, and Er; the main rare earth oxide Y 2 O 3 The molar ratio between the two auxiliary rare earth oxides is not equal, but the molar ratio between the auxiliary rare earth oxides is equal.

[0007] As an improvement, the particle size of the multi-component rare earth zirconium oxide material is less than 0.15 mm.

[0008] The present invention also provides a method for preparing the multi-component rare earth zirconium oxide material resistant to molten sand and dust erosion, which specifically comprises the following steps: 1) Based on the predetermined oxide component molar ratio, accurately calculate Y 2 O 3 , A 2 O 3 , B 2 O 3 and ZrO 2 The amount of each raw material required for the powder is weighed Y 2 O 3 , A2 O 3 , B 2 O 3 and ZrO 2 The powder is ball-milled to obtain a mixed slurry; 2) The mixed slurry is dried to remove excess ethanol, and then screened to ensure uniform particle size of the powder. The treated powder is subjected to a solid phase reaction at high temperature to synthesize a multi-component rare earth zirconium oxide material that is resistant to molten sand and dust erosion.

[0009] As an improvement, in step 1), Y 2 O 3 , A 2 O 3 , B 2 O 3 and ZrO 2 The powder is nano-grade powder, the powder particle size is ≤50nm, and the powder purity is ≥99.9%.

[0010] As an improvement, in step 1), the ball milling conditions are: the powders are added into a ball mill in sequence, and an appropriate amount of ball milling beads and a solvent are added as a mixed medium, wherein the mass ratio of the ball milling beads, the powder and the solvent is 3:1:2 to 6:1:3, the rotation speed is 130 to 160 rpm, and the time is 12 to 24 h. The main function of the ball milling process is to mix the powder materials evenly and reduce agglomeration through mechanical force. In the ball milling process, the number of grinding balls, the proportion of materials, the amount of solvent, the ball milling speed, and the time setting all directly affect the uniformity and dispersion of the powder.

[0011] As an improvement, in step 2), after drying at 80-100°C, the material is sieved through a 40-mesh sieve.

[0012] As an improvement, in step 2), the high-temperature solid phase reaction is first heated to 800-1000 °C and kept at this temperature for 1-4 h, then heated to 1200-1400 °C and kept at this temperature for 1-4 h, and finally cooled with the furnace. As an improvement, the multi-component rare earth zirconia material in the above step 2) is further ground and sieved, and then formed by dry pressing. The formed block is sintered at high temperature to obtain a dense multi-component rare earth zirconia ceramic block material.

[0013] As an improvement, the mesh number of the above sieve is 150 mesh, and the multi-component powder material is dry-pressed with a manual hydraulic press at a uniaxial pressure of 200 MPa for 30 to 60 seconds. The diameter of the green billet is 10-25.4 mm and the thickness is not less than 1 mm.

[0014] Using 200 MPa uniaxial pressure for dry pressing helps the powder to be uniformly densified during the molding process and reduce the formation of pores and cracks. This pressure value ensures the mechanical strength of the green billet and the powder can maintain a stable shape during the sintering process.

[0015] As an improvement, the sintering temperature is 1500~1600 ℃ and the time is not less than 20 hours. As an improvement, the mesh number of the above sieving is 100-200 meshes.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a multi-component rare earth zirconia material resistant to molten sand and dust erosion, which adopts a multi-component rare earth zirconia design. 2 O 3 Main rare earth oxides, A 2 O 3 and B 2 O 3 The main rare earth oxide is a secondary rare earth oxide. The main rare earth oxide and the secondary rare earth oxide are in a non-equimolar ratio, and the secondary rare earth oxides are in an equimolar ratio. 2 O 3 With two kinds of auxiliary rare earth oxides A 2 O 3 and B 2 O 3 The molar ratios of the main and auxiliary rare earth oxides are not equal, and the molar ratios of the auxiliary rare earth oxides are equal. This specific ratio makes the chemical composition of the material more stable, which helps to improve the material's resistance to molten sand and dust erosion by utilizing the synergistic effect of the main and auxiliary rare earths. The chemical formula of the multi-component rare earth zirconium oxide material is (xY 2 O 3 -yA 2 O 3 -yB 2 O 3 )-(1-x-2y)ZrO 2 , where the main rare earth oxide Y 2 O 3It imparts stability in the crystal structure, enhances the structural stability of the material and its ability to resist molten sand and dust erosion, and the addition of auxiliary rare earth oxides can adjust the lattice structure and physical properties of the material. The combined effect of different ion radii and lattice distortion can increase the scattering effect of the lattice, thereby reducing the thermal conductivity of the material and improving the thermal insulation performance of the coating. The present invention uses the collaborative design of multi-component rare earth elements. The advantage of the synergistic effect of multi-component rare earths is that it can solve the insufficient performance of a single rare earth material in a high-temperature environment and provide better comprehensive performance. By optimizing the composition ratio of the main rare earth and the auxiliary rare earth, and combining the advantages of multiple rare earth elements, a new type of multi-component rare earth zirconium oxide thermal barrier coating material is developed, which improves the thermal barrier coating's resistance to molten sand and dust erosion, low thermal conductivity and thermal stability. The present invention solves the technical problems of high thermal conductivity, insufficient resistance to molten sand and dust erosion, and poor thermal stability of thermal barrier coating materials.

[0017] The present invention also provides a method for preparing a multi-component rare earth zirconium oxide material resistant to molten sand and dust erosion, comprising: 2 O 3 , A 2 O 3 , B 2 O 3 and ZrO 2 , the ternary rare earth zirconia material is synthesized by high temperature solid phase reaction method, and then the multi-component rare earth zirconia dense ceramic block resistant to molten sand dust erosion is obtained by dry pressing and high temperature sintering. First, the molar percentage of the main rare earth oxide is controlled to 17≤x≤31%, which can ensure the structural stability of the rare earth zirconia thermal barrier coating material under high temperature corrosion conditions; the total molar percentage of the auxiliary rare earth oxide is controlled to 3<2y<17%. The addition of auxiliary rare earth oxide can adjust the lattice structure and physical properties of the material. The scattering effect of the lattice can be increased through the combined effect of different ion radii and lattice distortion, thereby reducing the thermal conductivity of the material and improving the thermal insulation performance of the coating; ensuring that the molar percentage of (x+2y) is between 34-46%, the effects of the main rare earth oxide and the auxiliary rare earth oxide can be balanced, and the comprehensive performance of the material can be enhanced, including low thermal conductivity, high temperature phase stability and resistance to molten sand dust erosion, and it is helpful to form a more stable oxide phase, reduce the erosion and penetration of the coating material by molten CMAS, and improve the resistance to molten sand dust. Secondly, a solid phase reaction is carried out at high temperature to synthesize the multi-component rare earth zirconium oxide material from the powder. This step is the key step in the formation of the material. The high temperature promotes the chemical reaction between the oxides to form the required multi-component rare earth zirconium oxide material.

[0018] Furthermore, the original powder particle size of the multi-element rare earth zirconia material is ≤50nm, the purity is ≥99.9%, and the use of nano-scale powder (≤50nm) can significantly improve the reactivity and sintering density of the material. On the one hand, the smaller particle size provides a larger specific surface area, which promotes the uniform dispersion and reaction between the components. This helps to obtain a more uniform microstructure and avoid performance defects caused by uneven distribution of large particles; powders with a purity of ≥99.9% can reduce the introduction of impurities and avoid impurities causing material performance degradation under high temperature environments. On the other hand, due to the high surface energy and reactivity of nanoparticles, the use of nanomaterials for high-temperature solid-phase reactions can usually complete the same reaction at a lower temperature. This not only saves energy, but also reduces the requirements for equipment and reduces production costs. At the nanoscale, the microstructure and component distribution of the material are more uniform. The use of nanomaterials can more easily control the composition and uniformity of the material, avoiding the problem of component segregation caused by larger particles in traditional preparation methods. At the same time, nanoparticles can form a dense microstructure through diffusion or sintering at high temperatures, which can significantly improve the durability and corrosion resistance of the material. Experiments show that multi-rare earth zirconium oxide materials are better than NASA's ZrO 2 -9.5Y 2 O 3 -2.25Gd 2 O 3 -2.25Yb 2 O 3 The molten sand and dust corrosion depth of multi-component ceramic materials and gadolinium zirconate materials is lower, and they are more suitable for service in environmental sand and dust conditions. At the same time, after the multi-component rare earth zirconia material of the present invention is corroded by molten sand and dust at 1400 ° C, a dense ternary rare earth silicate barrier layer (Y-Yb-Gd) Si is formed. 2 O 7 As well as the calcium-rich apatite network layer (the product of the reaction and crystallization of multi-rare earth zirconium oxide and molten sand and dust), it effectively blocks the penetration of molten sand and dust, inhibits grain boundary corrosion, and has excellent resistance to molten sand and dust erosion. It is expected to enhance its ability to resist environmental sand and dust corrosion in the harsh turbine service environment in the field of thermal barrier coatings.

[0019] Furthermore, the mass ratio of ball milling beads, powder and solvent is controlled to 3:1:2 ~ 6:1:3, the rotation speed is 130~160rpm, and the time is 12~24 hours. These parameters enable the powder to be fully mixed and avoid excessive ball milling leading to too fine particles or powder agglomeration. By precisely controlling the ball milling parameters, the material's component distribution is more uniform, which is conducive to subsequent sintering densification and uniform phase formation, thereby improving the comprehensive performance of the material.

[0020] Furthermore, the high-temperature solid-phase reaction causes each oxide powder to fully react at high temperature to generate the target multi-component rare earth zirconium oxide material. By first heating to 800~1000℃ and keeping it warm for 1~4 hours, it helps to remove surface adsorbents and residual stress in the powder. Then the temperature is raised to 1200~1400℃ and kept warm for 1~4 hours. This stage is the main reaction temperature to ensure that each component fully reacts. The furnace cooling method can avoid microcracks in the material caused by thermal stress caused by too fast cooling. Through staged heating and insulation treatment, the full reaction of each component and the densification of the material are ensured. Furnace cooling avoids thermal stress concentration during the cooling process and enhances the mechanical strength and thermal stability of the material.

[0021] Furthermore, the multi-component rare earth zirconia material is sintered at high temperature to obtain a dense multi-component rare earth zirconia ceramic block, and the high temperature sintering ensures the stability and corrosion resistance of the material.

[0022] Furthermore, the sintering temperature is set to 1500℃ and lasts for at least 20 hours, which ensures the full sintering of the material and the moderate growth of the grains, ensuring the density and high-temperature performance of the final material. High-pressure molding and long-term sintering make the material structure dense and low in porosity, and improve the material's resistance to molten sand and dust erosion.

[0023] The multi-component rare earth zirconium oxide material provided by the present invention has more excellent corrosion resistance under extremely high temperatures. At the same time, this patented material can remain stable at 1400°C, and is more suitable for the application of high-performance thermal barrier coatings in the next generation of ultra-high temperature aircraft engines or high-temperature gas turbines. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Prepared in Example 1 of the present invention XRD schematic diagram of the material; Figure 1a This is a surface microscopic morphology diagram of Example 1; Figure 1b Prepared in Example 1 Corrosion depth map of materials; Figure 1c Prepared in Example 1 Materials and Comparative Example 1 ZrO reported by NASA 2 -9.5Y 2 O 3 -2.25Gd 2 O 3 -2.25 Yb 2 O 3 Comparison of corrosion depth of molten sand and dust of multi-element zirconia materials; Figure 2 Prepared in Example 2 XRD schematic diagram of the material; Figure 2a This is a surface microscopic morphology image of Example 2; Figure 2b Prepared in Example 2 Materials and Comparative Example 1 ZrO reported by NASA 2 -9.5Y 2 O 3 -2.25Gd 2 O 3 -2.25 Yb 2 O 3 Comparison of corrosion depth of molten sand and dust of multi-element zirconia materials; Figure 3 Prepared in Example 3 XRD schematic diagram of the material; Figure 3a This is the surface microscopic morphology of Example 3; Figure 3b Prepared in Example 3 Materials and Comparative Example 2 Gadolinium zirconate (Gd 2 Zr 2 O 7 ) Comparison of molten sand dust corrosion depth; Figure 3c For comparative example 2, gadolinium zirconate (Gd 2 Zr 2 O 7 ) Penetration EDS-Mapping diagram; Figure 4 Prepared by Example 4 of the present invention XRD schematic diagram of the material; Figure 4a This is a surface microscopic morphology image of Example 4; Figure 4b Prepared in Example 4 Materials and Comparative Example 2 Gadolinium zirconate (Gd 2 Zr 2 O 7 ) Comparison of molten sand dust corrosion depth. DETAILED DESCRIPTION

[0025] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0026] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0027] The present invention is further described in detail below with reference to the accompanying drawings and embodiments: The present invention provides a multi-component rare earth zirconium oxide thermal barrier coating material resistant to molten sand and dust erosion, wherein the multi-component rare earth zirconium oxide thermal barrier coating material resistant to molten sand and dust erosion is specifically composed of nano Y 2 O 3 Powder, nano A 2 O 3 Powder, nano B 2 O 3 Powder and nano ZrO 2 The powder is used as raw material, and the required multi-component rare earth zirconia ceramic powder is prepared through a high-temperature solid phase reaction method, and a dense block of multi-component rare earth zirconia is obtained through dry pressing and high-temperature sintering.

[0028] The nano Y used in the multi-element rare earth zirconium oxide thermal barrier coating material resistant to molten sand and dust erosion 2 O 3 Powder, Nano A 2 O 3 Powder, nano B 2 O 3 Powder and nano ZrO 2 The powder particle size is ≤50nm and the powder purity is ≥99.9%.

[0029] The multi-element rare earth zirconium oxide thermal barrier coating material resistant to molten sand and dust erosion is expressed as (xY 2 O 3 -yA 2 O 3 -yB 2 O 3 )-(1-x-2y)ZrO 2 , where x and y represent the molar percentage of the main rare earth oxide and the auxiliary rare earth oxide, respectively.

[0030] The multi-component rare earth zirconium oxide thermal barrier coating material resistant to molten sand and dust erosion has the characteristics of low thermal conductivity and excellent resistance to molten sand and dust erosion.

[0031] Example 1 1) First, based on the predetermined molar ratio of the oxide components in the multi-component rare earth zirconia, the amount of each raw material required for the multi-component ceramic is accurately calculated, and then the nano-scale Y 2 O 3 , Yb 2 O 3 (Ytterbium oxide), Gd 2 O 3 (gadolinium oxide) and ZrO 2 Powder. Pour the four nanopowders into the ball mill in turn, and add appropriate amount of ball mill beads and anhydrous ethanol as the mixing medium; 2) Place the filled ball mill jar in a ball mill and perform ball milling to obtain a uniform mixed slurry; 3) The mixed slurry obtained after ball milling is dried to remove excess ethanol, and then screened to ensure uniform particle size of the powder. The treated powder is subjected to solid phase reaction at high temperature to synthesize multi-component rare earth zirconium oxide material; 4) The synthesized multi-element rare earth zirconium oxide material is further ground and sieved, and then formed by dry pressing. The formed block is sintered at high temperature to form a material with resistance to molten sand dust erosion. Dense multi-element rare earth zirconia ceramic material, among which Y 2 O 3 , Yb 2 O 3 , Gd 2 O 3 The mole percentages are 27%, 6%, and 6% respectively, and the rest is zirconium oxide; 5) Grind and polish the surface of the obtained multi-element rare earth zirconia block, mix the sand dust powder with an appropriate amount of anhydrous ethanol and evenly deposit it on the surface of the polished ceramic block, and after drying, put it into a high-temperature furnace for molten sand dust corrosion.

[0032] The nano Y 2 O 3 The powder particle size is 30nm and the purity is 99.999%; nano Yb 2 O 3 The powder particle size is 50nm and the purity is 99.9%; nano Gd 2 O 3 The powder particle size is 30nm and the purity is 99.9%; nano ZrO 2 The powder particle size is 20 nm and the purity is 99.9%.

[0033] In the steps 1) and 2), the ratio of the grinding balls in the ball mill: the material: the solvent is 5:1:2, the rotation speed is 145 rpm, and the time is 12 h. In the step 3), the drying temperature is 85°C, and the high temperature solid phase reaction is first heated to 1000°C at a heating rate of 10°C / min and kept at this temperature for 2 hours, then heated to 1300°C at a heating rate of 5°C / min and kept at this temperature for 2 hours, and finally cooled with the furnace. The mesh size of the sieve in step 4) is 150 mesh, and the multi-element powder is dry-pressed with a manual hydraulic press at a uniaxial pressure of 200 MPa for 60 seconds, and the green billet has a diameter of 10 mm and a thickness of 1 mm. The sintering temperature is 1550 °C and the sintering time is 20 h. In step 5), the volume ratio of the sand dust powder to the alcohol is 1:2, and the deposition density of the sand dust on the surface of the ceramic block is 30 mg / cm 2 After the sand and dust are deposited, the drying temperature is 85℃. The heating rate of the high temperature furnace is 10℃ / min below 1000℃ and 5℃ / min between 1000-1400℃. After constant temperature insulation, the cooling rate above 1000℃ is 5℃ / min, and then the power is turned off to cool with the furnace.

[0034] Comparative Example 1: The material preparation steps shown in this comparative example 1 differ from those shown in Example 1 in that: In step 1, according to the ZrO reported by NASA 2 -9.5Y 2 O 3 -2.25Gd 2 O 3 -2.25Yb 2 O 3 Multi-element zirconium oxide material: weigh an appropriate amount of nano-scale Y 2 O 3 , Yb 2 O 3 , Gd 2 O 3 and ZrO 2 Powders (molar percentages are 9.5%, 2.25%, 2.25%, and 86%, respectively), and the rest are the same as in Example 1.

[0035] Depend on Figure 1 It can be seen that the multi-component rare earth zirconia material synthesized by the high temperature solid phase reaction method has characteristic peaks (111), (220), and (200) of the defective fluorite structure, so the multi-component rare earth zirconia ceramic is a defective fluorite phase; Figure 1a As shown in Figure 2, the ceramic surface is dense and has a low porosity; Figure 1bAs shown in Figure 1, the corrosion depth of the material at 1400°C for 20 hours is only 5.64 μm, indicating that the thermal stability and corrosion resistance of the material have been significantly improved; Figure 1c As shown, when the material of Example 1 is corroded by molten sand dust at 1400°C, needle-shaped (Y-Yb-Gd) 2 Si 2 O 7 and the apatite phase distributed in the subsurface network (RE 8 Ca 2 Si 6 O 28 ,RE is a rare earth element) and fluorite phase. The ternary rare earth silicate precipitation phase on the surface and the network-distributed apatite phase and fluorite phase can jointly resist the corrosion of molten sand dust in the early stage. At high temperature, as the corrosion time increases, the (Y-Yb-Gd) 2 Si 2 O 7 It continues to grow and finally forms a dense and continuous protective layer to block further erosion by molten sand and dust. It exists for a long time and has a more stable structure, which can provide continuous resistance to erosion by molten sand and dust. The network-like distributed fluorite phase is the product of the decomposition of the ternary rare earth zirconium oxide of the matrix after being corroded by molten sand and dust, and its own anti-erosion effect is relatively low. In addition, as the molten sand and dust continue to corrode the material in Comparative Example 1, a zircon phase precipitates on the surface, and the grain boundaries are gradually dissolved. As the corrosion time increases, the molten sand and dust will continue to corrode and dissolve along the grain boundaries and penetrate into the interior of the material. Compared with Example 1, the zircon phase precipitated on the surface of Comparative Example 1 cannot provide protection against erosion by molten sand and dust, and the penetration depth is much higher than that of Example 1 at the same time, which shows that Example 1 has excellent resistance to molten sand and dust penetration.

[0036] Example 2 1) First, based on the predetermined molar ratio of the oxide components in the multi-component rare earth zirconia, the amount of each raw material required for the multi-component ceramic is accurately calculated, and then the nano-scale Y 2 O 3 、Dy 2 O 3 , Er 2 O 3 and ZrO 2 Powder. Pour the four nanopowders into the ball mill in turn, and add appropriate amount of ball mill beads and anhydrous ethanol as the mixing medium; 2) Place the filled ball mill jar in a ball mill and perform ball milling to obtain a uniform mixed slurry; 3) The mixed slurry obtained after ball milling is dried to remove excess ethanol, and then screened to ensure uniform particle size of the powder; the treated powder is subjected to a solid phase reaction at high temperature to synthesize a multi-component rare earth zirconium oxide material; 4) The synthesized multi-element rare earth zirconium oxide powder is further ground and sieved, and then formed by dry pressing. The formed block is sintered at high temperature to form a block with resistance to molten sand dust erosion. Dense multi-element rare earth zirconia ceramic material, among which Y 2 O 3 ,Dy 2 O 3 , Er 2 O 3 The molar percentages are 24%, 5%, and 5% respectively, and the rest is zirconium oxide; 5) Grind and polish the surface of the obtained multi-element rare earth zirconia block, mix the sand dust powder with an appropriate amount of anhydrous ethanol and evenly deposit it on the surface of the polished ceramic block, and after drying, put it into a high-temperature furnace for molten sand dust corrosion.

[0037] The nano Y 2 O 3 The powder particle size is 30nm and the purity is 99.999%; nano Dy 2 O 3 The powder particle size is 50nm and the purity is 99.9%; 2 O 3 The powder particle size is 50nm and the purity is 99.9%; nano ZrO 2 The powder particle size is 20 nm and the purity is 99.9%.

[0038] In the steps 1) and 2), the ratio of the grinding balls in the ball mill: the material: the solvent is 3:1:2, the rotation speed is 130 rpm, and the time is 24 hours. In the step 3), the drying temperature is 82°C, and the high temperature solid phase reaction is first heated to 800°C and kept for 1 hour, then heated to 1200°C and kept for 1 hour, and finally cooled with the furnace. The mesh size of the sieve in step 4) is 100 mesh, and the multi-element powder is dry-pressed with a manual hydraulic press at a uniaxial pressure of 200 MPa for 30 seconds, with a green blank having a diameter of 15 mm and a thickness of 3 mm. The sintering temperature is 1500 °C and the sintering time is 22 h.

[0039] In step 5), the volume ratio of the powder to the alcohol is 1:2, and the deposition density of the sand on the surface of the ceramic block is 30 mg / cm 2After the sand and dust are deposited, the drying temperature is 85℃. The heating rate of the high temperature furnace is 10℃ / min below 1000℃ and 5℃ / min between 1000-1400℃. After constant temperature insulation, the cooling rate above 1000℃ is 5℃ / min, and then the power is turned off to cool with the furnace.

[0040] Depend on Figure 2 It can be seen that the multi-component rare earth zirconia material synthesized by the high temperature solid phase reaction method has characteristic peaks (111), (220), and (200) of the defective fluorite structure, so the multi-component rare earth zirconia ceramic is a defective fluorite phase; Figure 2a As shown in Figure 2, the ceramic surface is dense and has a low porosity; Figure 2b As shown, when the material of Example 2 is corroded by molten sand dust at 1400°C, granular (Y-Dy-Er) 2 Si 2 O 7 As well as the apatite phase and fluorite phase distributed in the subsurface network. The ternary rare earth silicate precipitation phase on the surface and the apatite phase and fluorite phase distributed in the network can jointly resist the corrosion of molten sand dust in the early stage. At high temperature, as the corrosion time increases, the (Y-Dy-Er) at the solid-liquid interface 2 Si 2 O 7 It continues to grow and finally forms a dense and continuous protective layer to block further erosion by the molten sand and dust. It has a long existence time and a more stable structure, which can provide continuous resistance to erosion by the molten sand and dust. In addition, in some areas, a small amount of zircon phase will precipitate at the interface due to the dissolution of Zr in the molten sand and dust. The network-like distributed fluorite phase is the product of the decomposition of the ternary rare earth zirconium oxide of the matrix after being corroded by the molten sand and dust, and its own anti-erosion effect is relatively low. In addition, with the continuous corrosion of the molten sand and dust in Comparative Example 1, a zircon phase precipitates on the surface, and the grain boundaries are gradually dissolved. As the corrosion time increases, the molten sand and dust will continue to corrode and dissolve along the grain boundaries and penetrate into the interior of the material. Compared with Example 2, the material of Comparative Example 1 cannot provide protection against erosion by molten sand and dust, and the penetration depth is much higher than that of Example 2 at the same time, which shows that Example 2 has excellent resistance to molten sand and dust penetration.

[0041] Example 3 1) First, based on the predetermined molar ratio of the oxide components in the multi-component rare earth zirconia, the amount of each raw material required for the multi-component ceramic is accurately calculated, and then the nano-scale Y 2 O 3 、Dy 2 O 3 , Yb 2 O 3 and ZrO 2Powder. Pour the four nanopowders into the ball mill in turn, and add appropriate amount of ball mill beads and anhydrous ethanol as the mixing medium; 2) Place the filled ball mill jar in a ball mill and perform ball milling to obtain a uniform mixed slurry; 3) The mixed slurry obtained after ball milling is dried to remove excess ethanol, and then screened to ensure uniform particle size of the powder. The treated powder is subjected to solid phase reaction at high temperature to synthesize multi-component rare earth zirconium oxide material; 4) The synthesized multi-element rare earth zirconium oxide material is further ground and sieved, and then formed by dry pressing. The formed block is sintered at high temperature to form a material with resistance to molten sand dust erosion. Dense multi-element rare earth zirconia ceramic material, among which Y 2 O 3 ,Dy 2 O 3 , Yb 2 O 3 The molar percentages are 24%, 5%, and 5% respectively, and the rest is zirconium oxide; 5) Grind and polish the surface of the obtained multi-element rare earth zirconia block, mix the sand dust powder with an appropriate amount of anhydrous ethanol and evenly deposit it on the surface of the polished ceramic block, and after drying, put it into a high-temperature furnace for molten sand dust corrosion.

[0042] The nano Y 2 O 3 The powder particle size is 30nm and the purity is 99.999%; nano Dy 2 O 3 The powder particle size is 50nm and the purity is 99.9%; nano Yb 2 O 3 The powder particle size is 50nm and the purity is 99.9%; nano ZrO 2 The powder particle size is 20 nm and the purity is 99.9%.

[0043] In the steps 1) and 2), the ratio of the grinding balls in the ball mill is 6:1:3, the rotation speed is 160 rpm, and the time is 12 hours. In the step 3), the drying temperature is 85°C, and the high-temperature solid phase reaction is first heated to 1000°C at a heating rate of 10°C / min and kept at this temperature for 4 hours, then heated to 1400°C at a heating rate of 5°C / min and kept at this temperature for 4 hours, and finally cooled in the furnace. The mesh size of the sieve in step 4) is 160 meshes, and the multi-element powder is dry-pressed with a manual hydraulic press at a uniaxial pressure of 200 MPa for 30 seconds, with a green blank diameter of 20 mm and a thickness of 4 mm. The sintering temperature is 1600 °C and the sintering time is 24 h. In step 5), the volume ratio of the powder to the alcohol is 1:2, and the deposition density of the sand on the surface of the ceramic block is 30 mg / cm 2 After the sand and dust are deposited, the drying temperature is 85℃. The heating rate of the high temperature furnace is 10℃ / min below 1000℃ and 5℃ / min between 1000-1400℃. After constant temperature insulation, the cooling rate above 1000℃ is 5℃ / min, and then the power is turned off to cool with the furnace.

[0044] Comparative Example 2: The material preparation steps shown in this comparative example 2 and example 3 are different in that: In step 1, according to gadolinium zirconate (Gd 2 Zr 2 O 7 ) with a stoichiometric ratio of 1:2 in molar ratio. 2 O 3 and ZrO 2 Powder, the rest is the same as Example 3.

[0045] Depend on Figure 3 It can be seen that the multi-component rare earth zirconia material synthesized by the high temperature solid phase reaction method has characteristic peaks (111), (220), and (200) of the defective fluorite structure, so the multi-component rare earth zirconia ceramic is a defective fluorite phase; Figure 3a As shown in Figure 2, the ceramic surface is dense and has a low porosity; Figure 3b As shown, in the process of molten sand dust corrosion at 1400℃, granular (Y-Dy-Yb) is first precipitated on the surface of Example 3. 2 Si 2 O 7 As well as the apatite phase and fluorite phase distributed in the subsurface network. The ternary rare earth silicate precipitation phase on the surface and the apatite phase and fluorite phase distributed in the network can jointly resist the corrosion of molten sand dust in the early stage. At high temperature, as the corrosion time increases, the (Y-Dy-Yb) at the solid-liquid interface 2 Si 2 O 7 It continues to grow and finally forms a dense and continuous protective layer to block the further erosion of the molten sand dust. It has a long existence time and a more stable structure, which can provide continuous resistance to the erosion of the molten sand dust. In addition, in some areas, due to the dissolution of Zr in the molten sand dust, a small amount of zircon phase (ZrSiO 4 The network-like distribution of fluorite phase is the product of the decomposition of the ternary rare earth zirconium oxide matrix after being corroded by the molten sand dust, and its own anti-corrosion effect is relatively low. In addition, it can be seen from Comparative Example 2 that there is a large corrosion depth at the beginning of corrosion. With the continuous erosion of the molten sand dust, scattered zircon phases (ZrSiO 4), and the subsurface layer is composed of alternating two-phase networks of gadolinium silicate and gadolinium-doped zirconia. Figure 3c As shown, through the surface scanning of the energy spectrum, it can be seen that the silicon element in the molten sand and dust penetrates into the matrix material in large quantities, showing poor corrosion resistance. In the upper part of the corrosion area, the molten sand and dust are accelerated to penetrate into the matrix due to the dissolution of the grain boundaries, and the corrosion is relatively severe. In the lower part of the corrosion area, it can be seen that there is an enrichment of aluminum elements, and a three-phase coexistence zone composed of gadolinium aluminum perovskite, gadolinium silicate and gadolinium-doped zirconia is formed on the side close to the uncorroded area of ​​the matrix. As the corrosion time increases, the molten sand and dust will continue to dissolve the matrix material through reaction corrosion, and the corrosion is more severe. In Comparative Example 2, the reaction precipitation phase, whether it is the zircon phase, the gadolinium silicate or the gadolinium aluminum perovskite structure precipitation phase, does not show resistance to molten sand and dust. Compared with Example 3, it cannot provide protection against molten sand and dust erosion, and the penetration depth is much higher than that of Example 3 at the same time, which shows that the material of Example 3 has excellent resistance to molten sand and dust penetration.

[0046] Example 4 1) First, based on the predetermined molar ratio of the oxide components in the multi-component rare earth zirconia, the amount of each raw material required for the multi-component ceramic is accurately calculated, and then the nano-scale Y 2 O 3 , Yb 2 O 3 , Gd 2 O 3 and ZrO 2 Powder. Pour the four nanopowders into the ball mill in turn, and add appropriate amount of ball mill beads and anhydrous ethanol as the mixing medium; 2) Place the filled ball mill jar in a ball mill and perform ball milling to obtain a uniform mixed slurry; 3) The mixed slurry obtained after ball milling is dried to remove excess ethanol, and then screened to ensure uniform particle size of the powder. The treated powder is subjected to solid phase reaction at high temperature to synthesize multi-component rare earth zirconium oxide powder; 4) The synthesized multi-element rare earth zirconium oxide powder is further ground and sieved, and then formed by dry pressing. The formed block is sintered at high temperature to form a block with resistance to molten sand dust erosion. Dense multi-element rare earth zirconia ceramic material, among which Y 2 O 3 , Yb 2 O 3 , Gd 2 O 3 The molar percentages are 30%, 7%, and 7% respectively, and the rest is zirconium oxide; 5) Grind and polish the surface of the obtained multi-element rare earth zirconia block, mix the sand dust powder with an appropriate amount of anhydrous ethanol and evenly deposit it on the surface of the polished ceramic block, and after drying, put it into a high-temperature furnace for molten sand dust corrosion.

[0047] The nano Y 2 O 3 The powder particle size is 30nm and the purity is 99.999%; nano Yb 2 O 3 The powder particle size is 50nm and the purity is 99.9%; nano Gd 2 O 3 The powder particle size is 30nm and the purity is 99.9%; nano ZrO 2 The powder particle size is 20 nm and the purity is 99.9%.

[0048] In the steps 1) and 2), the ratio of the grinding balls in the ball mill: the material: the solvent is 4:1:2, the rotation speed is 145 rpm, and the time is 15 hours. In the step 3), the drying temperature is 90°C, and the high-temperature solid phase reaction is first heated to 1000°C at a heating rate of 10°C / min and kept at this temperature for 2 hours, then heated to 1300°C at a heating rate of 5°C / min and kept at this temperature for 2 hours, and finally cooled in the furnace. The mesh size of the sieve in step 4) is 200 mesh, and the multi-element powder is dry-pressed with a manual hydraulic press at a uniaxial pressure of 200 MPa for 60 seconds. The green billet has a diameter of 25.4 mm and a thickness of 2 mm. The sintering temperature is 1580 °C and the sintering time is 20 h. In step 5), the volume ratio of the powder to the alcohol is 1:2, and the deposition density of the sand on the surface of the ceramic block is 30 mg / cm 2 After the sand and dust are deposited, the drying temperature is 90℃. The heating rate of the high temperature furnace is 10℃ / min below 1000℃ and 5℃ / min between 1000-1400℃. After constant temperature insulation, the cooling rate above 1000℃ is 5℃ / min, and then the power is turned off to cool with the furnace.

[0049] The material preparation steps shown in this comparative example 3 and example 4 are different in that: In step 1, according to gadolinium zirconate (Gd 2 Zr 2 O 7 ) with a stoichiometric ratio of 1:2 in molar ratio. 2 O 3 and ZrO 2 Powder, the rest is the same as Example 4.

[0050] Depend on Figure 4It can be seen that the multi-component rare earth zirconia material synthesized by the high temperature solid phase reaction method has characteristic peaks (111), (220), and (200) of the defective fluorite structure, so the multi-component rare earth zirconia ceramic is a defective fluorite phase; Figure 4a As shown in Figure 2, the ceramic surface is dense and has a low porosity; Figure 4b As shown, when the material of Example 4 is corroded by molten sand dust at 1400°C, granular (Y-Gd-Yb) is first precipitated on the surface. 2 Si 2 O 7 As well as the apatite phase and fluorite phase distributed in the subsurface network. The ternary rare earth silicate precipitation phase on the surface and the apatite phase and fluorite phase distributed in the network can jointly resist the corrosion of molten sand dust in the early stage. At high temperature, as the corrosion time increases, the (Y-Dy-Yb) at the solid-liquid interface 2 Si 2 O 7 It continues to grow and finally forms a dense and continuous protective layer to block the further erosion of the molten sand dust. It has a long existence time and a more stable structure, which can provide continuous resistance to the erosion of the molten sand dust. In addition, in some areas, due to the small amount of Zr dissolved in the molten sand dust, a small amount of zircon phase (ZrSiO 4 The network-like distribution of fluorite phase is the product of the decomposition of the ternary rare earth zirconium oxide matrix after being corroded by the molten sand dust, and its own anti-corrosion effect is relatively low. In addition, it can be seen from Comparative Example 2 that there is a large corrosion depth at the beginning of corrosion. With the continuous erosion of the molten sand dust, scattered zircon phases (ZrSiO 4 ), and the subsurface layer is composed of alternating two-phase networks of gadolinium silicate and gadolinium-doped zirconia. The upper part of the corrosion area is eroded more severely because the grain boundaries are dissolved, which accelerates the reaction and penetration of molten sand dust into the matrix. It can be seen that there is enrichment of aluminum in the lower part of the corrosion area, and a three-phase coexistence zone composed of gadolinium aluminum perovskite, gadolinium silicate and gadolinium-doped zirconia is formed on the side close to the uncorroded area of ​​the matrix. As the corrosion time increases, the molten sand dust will continue to dissolve the matrix material through reaction erosion, and the corrosion is more severe. In Comparative Example 2, the reaction precipitated phase, whether it is zircon phase, gadolinium silicate or gadolinium aluminum perovskite structure, does not show resistance to molten sand dust. Compared with Example 4, it cannot provide protection against molten sand dust erosion, and the penetration depth is much higher than that of Example 4 at the same time, which shows that Example 4 has excellent performance in resisting molten sand dust penetration.

[0051] With excellent anti-CMAS performance, the reaction barrier type gadolinium zirconate (Gd 2 Zr 2 O 7) materials, the defective fluorite structure in the ternary rare earth zirconia prepared by the present invention can provide oxygen vacancies, which is conducive to the migration of ions in a high temperature environment, thereby forming a stable and dense barrier layer (such as a calcium-rich apatite network layer and a ternary rare earth silicate layer) at the material interface. These barrier layers can effectively block the infiltration of molten sand and dust, reduce the corrosion of grain boundaries, and make the material have a more excellent resistance to molten sand and dust erosion, which can meet the material selection requirements of new high-performance thermal barrier coating materials.

[0052] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A multi-component rare earth zirconium oxide material resistant to molten sand and dust erosion, characterized in that: The chemical composition of the multi-component rare earth zirconium oxide material resistant to molten sand and dust erosion is: (xY2O3-yA2O3-yB2O3)-(1-x-2y)ZrO2, wherein the molar percentage x is: 17%≤x≤31%, the molar percentage y is: 1.5%<y<8.5%, and 34%≤(x+2y)≤46%; The multi-component rare earth zirconia material resistant to molten sand and dust erosion includes zirconium oxide, main rare earth oxide Y2O3, auxiliary rare earth oxide A2O3 and auxiliary rare earth oxide B2O3, wherein the rare earth element A or B in the auxiliary rare earth oxide A2O3 and the auxiliary rare earth oxide B2O3 includes any one of Gd, Dy, Yb, and Er; the main rare earth oxide Y2O3 and the two auxiliary rare earth oxides are in a non-equimolar ratio, while the auxiliary rare earth oxides are in an equimolar ratio.

2. The multi-component rare earth zirconium oxide material resistant to molten sand and dust erosion according to claim 1, characterized in that: The particle size of the multi-component rare earth zirconia material resistant to molten sand and dust erosion is less than 0.15 mm.

3. The method for preparing a multi-component rare earth zirconium oxide material resistant to molten sand and dust erosion according to any one of claims 1 to 2, characterized in that: The following steps are involved: 1) Weigh Y2O3, A2O3, B2O3 and ZrO2 powders according to the molar ratio of the oxide components and perform ball milling to prepare a mixed slurry; 2) Drying and sieving the mixed slurry to obtain powder, subjecting the powder to a solid phase reaction at high temperature to synthesize a multi-component rare earth zirconium oxide material resistant to molten sand and dust erosion.

4. The method for preparing a multi-component rare earth zirconium oxide material resistant to molten sand and dust erosion according to claim 3, characterized in that: In step 1), Y2O3, A2O3, B2O3 and ZrO2 powders are nano-scale powders, with a powder particle size of ≤50nm and a powder purity of ≥99.9%.

5. The method for preparing a multi-component rare earth zirconium oxide material resistant to molten sand and dust erosion according to claim 3, characterized in that: In step 1), the ball milling conditions are as follows: adding the powder into a ball mill jar, and adding an appropriate amount of ball milling beads and a solvent as a mixed medium, wherein the mass ratio of the ball milling beads, the powder and the solvent is 3:1:2 to 6:1:3, the rotation speed is 130 to 160 rpm, and the time is 12 to 24 h.

6. The method for preparing a multi-component rare earth zirconium oxide material resistant to molten sand and dust erosion according to claim 3, characterized in that: In step 2), the high temperature solid phase reaction is first heated to 800-1000°C and kept for 1-4 h, then heated to 1200-1400°C and kept for 1-4 h, and finally cooled with the furnace.

7. The method for preparing a multi-component rare earth zirconium oxide material resistant to molten sand and dust erosion according to claim 3, characterized in that: The multi-component rare earth zirconia material in step 2) is then ground and sieved, and then formed by dry pressing. The formed block is sintered at a high temperature to obtain a dense multi-component rare earth zirconia ceramic block material.

8. The method for preparing a multi-component rare earth zirconium oxide material resistant to molten sand and dust erosion according to claim 7, characterized in that: The dry pressing process includes: time of 30-60 s, green billet diameter of 10 mm-25.4 mm, and thickness of not less than 1 mm.

9. The method for preparing a multi-component rare earth zirconium oxide material resistant to molten sand and dust erosion according to claim 7, characterized in that: The sintering temperature is 1500~1600℃ and the time is not less than 20 h.

10. The method for preparing a multi-component rare earth zirconium oxide material resistant to molten sand and dust erosion according to claim 7, characterized in that: The mesh size for sieving is 100-200 mesh.

Citation Information

Patent Citations

  • Ternary rare earth doped YSZ thermal barrier coating material and preparation method thereof

    CN106588042A

  • Zirconia-based thermal barrier coating material with low thermal conductivity as well as preparation method and application of zirconium oxide-based thermal barrier coating material

    CN113045309A

  • Multi-element rare earth co-stabilized zirconia thermal spraying ceramic powder as well as preparation method and application thereof

    CN115784739A

  • Thermal barrier coating systems and processes therefor

    US20130095344A1

  • Thermal barrier coating systems and processes therefor

    US20140220378A1